Effectiveness of Progressive Muscle Relaxation on Pain and Sleep Quality in Lung Cancer Patients Undergoing Chemotherapy: A Quasi-Experimental Study - Mira, Mira; Daud, Izma; Ruwaida, Laiya; Mahmud, Mahmud; Ariani, Mahrida Dwi (Journal of Applied Nursing and Health, 2025)
Background: Pain and sleep disturbances are common among lung cancer patients undergoing chemotherapy, negatively affecting comfort and quality of life. Progressive Muscle Relaxation (PMR) is a non-pharmacological intervention that potentially alleviates these issues. However, few studies have specifically examined the effects of PMR on chemotherapy-induced symptoms in lung cancer patients, particularly in Indonesia. Methods: A quasi-experimental pretest–posttest study with a control group was conducted in Banjarmasin, Indonesia, involving 60 purposively selected lung cancer patients. Participants were assigned to an intervention group (n = 30) and a control group (n = 30). The intervention group performed daily PMR exercises for 14 consecutive days, while the control group received standard care. Pain was measured using the Numeric Rating Scale (NRS), and sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using the Wilcoxon signed-rank test, and ethical approval was obtained from the institutional review board. Results: Demographic characteristics were comparable between groups. After the intervention, pain levels decreased significantly in the intervention group, with 40% reporting mild pain and 53.3% moderate pain, compared to the control group, where 66.7% reported moderate pain and 33.3% severe pain. All participants in the intervention group achieved good sleep quality, while no improvements were observed in the control group. Between-group differences were statistically significant (p < 0.05). Conclusion: PMR effectively reduces pain and improves sleep quality in lung cancer patients undergoing chemotherapy. This study provides new evidence on the application of PMR in supportive care for lung cancer patients in Indonesia.